Induction Proof: Formula for Sum of n Fibonacci Numbers

I am stuck though on the way to prove this statement of fibonacci numbers by induction :

my steps:
definition: $F_{0}:=0, F_{1}:=1 $ and $F_{n}:=F_{n-1}+F_{n-2}$

The Hypothesis is: $\sum_{i=0}^{n} F_{i}=F_{n+2}-1$ for all $n > 1$

Base case: $n=2$
$\sum_{i=0}^{2} F_{i}=F_{0}+F_{1}+F_{2}=0+1+F_{1}+F_{0}=0+1+1+0=2$ which is equal to $F_{2+2}-1=F_{4}-1=F_{3}+F_{2}-1=F_{2}+F_{1}+F_{2}-1=1+1+1-1=2$ OK!

inductive step:
to prove: $\sum_{i=0}^{n+1} F_{i}=F_{n+3}-1$ for all $n > 1$
$\sum_{i=0}^{n+1} F_{i}=\sum_{i=0}^{n} F_{i}+F_{n+1}=F_{n+2}-1+F_{n+1}=…help…=F_{n+3}-1$

i need help to $..help..$ please! thanks a lot

Solutions Collecting From Web of "Induction Proof: Formula for Sum of n Fibonacci Numbers"